Restoration measures for foundations of metal silos on degraded loess soils - Kichasov, Oleksii (Academic journal Industrial Machine Building Civil Engineering, 2025)
This paper examines the restoration of the serviceability of foundations of steel silos located on wetted and degraded loess soils. Based on the survey results and the analysis of the recorded deformations, a sequence of engineering measures is presented, including local repair of the ring foundation, restoration of the underground gallery, strengthening of the anchor connections and replacement of the pavement. It is shown that the applied set of repair measures ensures the stabilisation of the foundation structures and allows continued operation of the silos without a complete shutdown. The effectiveness of the implemented measures is confirmed by the results of geotechnical and geodetic monitoring conducted after the completion of the repair works.